2007
DOI: 10.1007/s00425-006-0410-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus deficiency in red clover promotes exudation of orobanchol, the signal for mycorrhizal symbionts and germination stimulant for root parasites

Abstract: Plant derived sesquiterpene strigolactones, which have previously been characterized as germination stimulants for root parasitic plants, have recently been identified as the branching factors which induce hyphal branching morphogenesis, a critical step in host recognition by arbuscular mycorrhizal (AM) fungi. We show here that, in red clover plants (Trifolium pratense L.), which is known as a host for both AM fungi and the root holoparasitic plant Orobanche minor Sm., reduced supply of phosphorus (P) but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
251
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(265 citation statements)
references
References 26 publications
8
251
0
1
Order By: Relevance
“…This is in agreement with measurements of Yoneyama et al (2007), in which higher levels of strigolactones were found in roots as compared to other tissues. Little is known about what controls the level of strigolactone synthesis, although light quality and intensity could be the determining factors (Koltai et al 2011).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with measurements of Yoneyama et al (2007), in which higher levels of strigolactones were found in roots as compared to other tissues. Little is known about what controls the level of strigolactone synthesis, although light quality and intensity could be the determining factors (Koltai et al 2011).…”
Section: Introductionsupporting
confidence: 92%
“…In contrast to lateral root formation, Pi-deficient inhibition of root growth occurs independently of strigolactone signaling, as evidenced by Pi-deficient inhibition of primary root growth in both max2 and wild type (Yoneyama et al 2007;Jain et al 2007;Mayzlish-Gati et al 2012).…”
Section: Strigolactones Increase Primary Root Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…[55][56][57][58] Hence, it is possible that SLs provide a way for the plant to coordinate shoot development with nutritional conditions.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 SLs play key roles in adaptive responses to N and P deficiencies due to elevated SL levels in roots. [13][14][15][16][17] For example, SLs promote symbioses with arbuscular mycorrhizal fungi by inducing hyphal branching and they adjust shoot architecture by inhibiting tiller bud outgrowth to better adapt to a P or N deficiency. 14,[16][17][18][19][20][21] Recently, it was reported that SLs regulate the perception or response of plants to P-limited conditions.…”
Section: Strigolactones (Sls) Regulate Root Developmentmentioning
confidence: 99%